What a good boy! Deciphering the efficiency of detection dogs - Martin, Clément; Willem, Noémie; Desablens, Sorenza; Menard, Vincent; Tajri, Sophia; Blanchard, Solène; Brostaux, Yves; Verheggen, François; Diederich, Claire (Frontiers in Analytical Science, 2022)
Dogs are renowned for their powerful olfactory abilities and are used in many police and military application fields, including detection of drugs, human remains and explosives. However, methods assessing dog’s performance (MAP) are scarce and have barely been validated, mainly because of the lack of scientific knowledge about post-training performance assessment. The first goal of this research is to define what an efficient detection dog (DD) is, since this is a necessary step to move to the second objective: developing a quantitative MAP. We associated results extracted from (i) an international survey sent to professional DD’s practitioners (n=50), and from (ii) an experimental assay performed on cadaver and drug DDs (n=20). Our international empirical survey allowed to define a performant detection dogs as a confident animal, that makes very few mistakes, alerting the presence of a target odor as close as possible, strategic to properly screen the searching area, independent and not easily distracted. Based on this definition, the developed quantitative MAP based on a video tracking of DD in a circular behavioral arena allowed to measure the error rate of detection dogs as well as the accuracy and the strategy level. Despite the lake of knowledge on this last parameters, we identify that, the level of strategy is mainly explained by the variance of some parameters as the frequency of the target zone visit, research time and research distance. The strategy is therefore a measure of repeatability of the dogs’ behavior in a known environment. Regarding other parameters, previous studies have already demonstrated that detection dogs are usually confidant. Finally, the guidance is not assessing during the developed MAP but handlers cannot guide the DD during the research session. Based on this method, future studies should follow DD performance’s evaluation during the entire training process. This performance monitoring would allow to determine thresholds value of important parameters to ease the identification of an efficient DDs, as well as to study the impact of some factors (such as dogs breed, gender and training aids used during DD conditioning) on their performances.